A study to estimate the knowledge and practice regarding safe sex among teenage girls attending a rural hospital - Haldar, Sanjana; Akhtar, Selim; Chowdhury, Srijoni; Chatterjee, Shiv S.; Dan, Utpal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: This work was planned to assess knowledge about sexually transmitted diseases (STDs), contraceptive methods available and the practice of use of contraceptives and personal hygiene among teenage girls attending the outpatient department (OPD) of a rural medical college. Methods: Consenting, non-pregnant teenage girls (14-19 years) attending the gynaecology and obstetrics OPD with minor ailments were asked to respond to a questionnaire and blinded data collection was done by two lady counsellors. Statistical analysis was performed. Results: Knowledge of STI, unwanted pregnancy and family planning was significantly higher in teenage girls with sexual exposure, and in those who had completed standard 12 education (p<0.001). Conclusions: Our work suggests that in this particular rural setting knowledge level of STD, HIV and unwanted pregnancy is high but practice of safe sex and contraceptives are low. We suggest implementation of age-appropriate gender based, culturally sensitive sex education curriculum in schools to cope up the increasing vulnerability of young girls. Additionally, community participation, health care institutions and media can raise awareness in teenage girls and their families and remove the taboo regarding family planning practices.